Tertulis dalam Tubuh, Ditulis Ulang oleh Kasih Karunia: Epigenetik sebagai Jembatan antara Sains dan Teologi Pemulihan - Immanuela Deru; Lia Lesty; Simon Simare-mare; Evi Sondag (Sekolah Tinggi Teologia Kerusso Indonesia, 2026)
This article explores the integration of epigenetics and Christian restoration theology as a new framework for understanding trauma and human restoration holistically. Epigenetics demonstrates that life experiences, particularly trauma, can influence gene expression without altering DNA structure and may even be transmitted across generations. Meanwhile, Christian restoration theology emphasizes the grace of God as a power that restores humanity completely in spiritual, psychological, relational, and embodied dimensions. This study employs a qualitative library research approach by examining recent scientific and theological literature relevant to trauma, epigenetic change, restoration, and Christian understandings of grace. The findings reveal that trauma leaves measurable biological imprints within the body, yet epigenetic changes remain reversible through healthy relationships, therapeutic interventions, and spiritual practices. These results indicate that human restoration should not be viewed only as an inward spiritual experience, but also as a holistic process involving psychological healing and biological renewal. Therefore, grace can be understood as a transformative power that works comprehensively within the spiritual, psychological, and biological dimensions of human existence, opening possibilities for intergenerational healing and renewed life for contemporary theological reflection.